2016
DOI: 10.1177/1938640016679701
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumor of Talus: T-Construct Method of Bone Grafting

Abstract: Therapeutic, Level IV: Case Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…A summary of 16 cases reported in 15 studies can be found in Table 1. Among 16 case studies, 56% of patients were within the 20-40-year-old age range [4,8,10,[13][14][15][16]18] while 31% were under 20 [6,7,11,12,17] and 13% were over 40 [5,9]. The ratio of male to female cases was 7:9 and the duration of symptoms ranged from one month to three years.…”
Section: Figure 5: Six-month Post-operative Radiograph Showing the Bo...mentioning
confidence: 99%
See 3 more Smart Citations
“…A summary of 16 cases reported in 15 studies can be found in Table 1. Among 16 case studies, 56% of patients were within the 20-40-year-old age range [4,8,10,[13][14][15][16]18] while 31% were under 20 [6,7,11,12,17] and 13% were over 40 [5,9]. The ratio of male to female cases was 7:9 and the duration of symptoms ranged from one month to three years.…”
Section: Figure 5: Six-month Post-operative Radiograph Showing the Bo...mentioning
confidence: 99%
“…Physical examination findings reported include pain, swelling and tenderness [5][6][7][8][9][10]12,13,[15][16][17][18]; an antalgic gait [6,10]; and painful and/or restricted range of motion at the ankle joint [4,7,8,10,13,15,16,18] or subtalar joint [6,8,13,15,16,18]. These symptoms are often severe enough to interfere with daily activities such as walking or a patient's ability to do sports.…”
Section: Figure 5: Six-month Post-operative Radiograph Showing the Bo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Giant cell tumor (GCT) is a benign, locally aggressive bone tumor rich in osteoclast‐like giant cells. It represents around 5‐6% of all primary bone neoplasms and 20% of benign bone neoplasms . GCTs tend to occur at the third and fourth decades of life, with a slightly higher incidence in women.…”
Section: Benign Lesionsmentioning
confidence: 99%